Validation of Resilience Assessment Tool 25 (RAT-25) - Amalia, Madihie; Nur Fatihah, Abdullah Bandar; Salmah, Mohamad Yusoff; Siti Norazilah, Mohd Said; Yow, Chong Lee; Fatahiah, Mat Hashim; Zanariah, Zain; Norlaily, Md Nasir; Wan Nurul Izza, Wan Husin; Hurilain Hasya, Naser (2022)
Being resilience in any adversities or crises is crucial especially after the COVID-19 outbreak among the adolescents. Resilience is an ability to adapt psychologically in order to learn bouncing back. The process to balance the protective factors and risk factors in improving adolescents’ mental health and wellbeing at school. Recent studies have revealed that identification of resilience domains such Basics, Belonging, Learning, Coping and Core Self influence the resiliency of individuals. There are limited resilience assessments. Hence, this study fills up the limitations by revising the current Resilience Assessment Tool 43 (RAT-43) to a shorter version as known Resilience Assessment Tool 25 (RAT-25) by considering the psychological need in adolescents in responding the items. RAT-25’s validity and reliability testing were performed with the recruitment from 13-year-olds, lower secondary students in Malaysia. The Exploratory Factor Analysis and Confirmatory Factor Analysis were performed to examine the construct validity particularly the factorial structure and reliability of this instrument. Results from the EFA yielded 5-factor structure. Similarly, results from the CFA using Structural Equation Modelling (AMOS) also validated the five-factor structure of RAT (B, B, L, C, CS). Findings also indicated that the measured items are reliable. The findings established that all five resilience domains are useful for assessing adolescents’ resilience. The implications for psychometric assessment were evident in terms of giving empirical evidence to corroborate theory-based constructs and also validating items' quality to appropriately represent the measurement.